2012
DOI: 10.1051/0004-6361/201118150
|View full text |Cite
|
Sign up to set email alerts
|

Dust and molecular shells in asymptotic giant branch stars

Abstract: Context. Asymptotic giant branch (AGB) stars are one of the largest distributors of dust into the interstellar medium. However, the wind formation mechanism and dust condensation sequence leading to the observed high mass-loss rates have not yet been constrained well observationally, in particular for oxygen-rich AGB stars. Aims. The immediate objective in this work is to identify molecules and dust species which are present in the layers above the photosphere, and which have emission and absorption features i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 161 publications
(243 reference statements)
3
41
0
Order By: Relevance
“…10), and has already been suggested to explain similar features seen in mid-infrared interferometric measurements of other comparable sources (e.g. Wittkowski et al 2007;Zhao-Geisler et al 2012).…”
Section: Morphology Of Rt Vir In the Mid-infraredsupporting
confidence: 62%
See 1 more Smart Citation
“…10), and has already been suggested to explain similar features seen in mid-infrared interferometric measurements of other comparable sources (e.g. Wittkowski et al 2007;Zhao-Geisler et al 2012).…”
Section: Morphology Of Rt Vir In the Mid-infraredsupporting
confidence: 62%
“…Finally, interferometric measurements in the mid-infrared have already pointed to the presence of Al 2 O 3 dust around two stellar radii in Mira and semi-regular M-type AGB stars (e.g. Wittkowski et al 2007;Zhao-Geisler et al 2012). We therefore decided to add corundum in the a-posteriori COMA radiative transfer computation, using the small-particle limit approximation.…”
Section: Exploring Extra Dust Opacitiesmentioning
confidence: 99%
“…Using image reconstruction techniques, Zhao-Geisler et al (2015) were able to spatially resolve the dust formation region close to the star and deduced that the data signal the presence of a dust layer of presumably amorphous aluminium oxide (Al 2 O 3 ) at ∼2 R . The observations suggest that the formation of amorphous Al 2 O 3 occurs mainly around or after visual minimum (Zhao-Geisler et al 2012).…”
Section: Infrared Continuum Emissionmentioning
confidence: 86%
“…While Norris et al (2012) found a halo of large (∼0.3 µm), transparent grains close to the photosphere (at r ≤ 2 R ) in a few O-rich AGBs, Zhao-Geisler et al (2012) reported evidence for the coexistence of a warm layer of H 2 O and a Al 2 O 3 dust shell close to the stellar surface in several O-rich evolved stars. The presence of two dust shells of alumina and silicate composition, where the alumina shell is located below the silicate shell, has been inferred from the observation of a few O-rich stars (ZhaoGeisler et al 2012;Karovicova et al 2013).…”
Section: Summary and Discussionmentioning
confidence: 99%